Analysis of the ratio between coordination and butterfly propulsion index for expert swimmers - Boulesteix, L.; Chollet, D. (2002)
The logic of the butterfly coordination for expert swimmers is associated with two undulations of legs for each complete arm cycle, whose coordination depends on the velocity`s increase (Chollet and Boulesteix, 2001). The aim of this study is to determine how this coordination`s change is linked to a relative increase of the propulsion, which is quantified by an Index of Butterfly Propulsion (IBP). METHODS The coordination`s study of eleven international swimmers is made thanks with three above and underwater front and profile cameras set a rapid shutter speed connected to a video timer. The protocol used was the one described by Chollet et al. (1998). Each swimmer performed 12.5m at four different swim paces : 400m (V400), 200m (V200), 100m (V100) and 50m (V50). The coordination is estimated by the temporal gap between the reference points, which delimit each cycle of the arms and legs. The Index of Butterfly Propulsion was calculated with a specific computer program based on the temporal gap (T) variations and the evolution of arm and leg phases. RESULTS The analysis of the structure of arm and leg coordination for the experts swimmers shows a significant decrease of the spatio-temporal relations T1 (gap between the entry of the hands in the water and the high break even point of the 1st undulation) and T2 (the gap between the beginning of the hand`s backwards movement and the low break-even point of the 1st undulation) passing from 5,31 ± 2.52% (V400) to 3.65 ± 4.09% (V50) for T1 (p<0.05) and from 15.18 ± 8.73% (V400) to 6.88 ± 4.34% (V50) for T2 (p<0.05). Parallel to the decrease of the spatio-temporal relations, the results showed an significant increase of propulsion index passing from 57.79 ± 6.34% (V400) to 66.22 ± 4.23% (V50). DICUSSION The increase of swimming velocity was associated by an increase in stroke rate and a decrease in stroke length and also an increase of the drag, with the progressive gap of the arm and leg coordination. The regular evolution of times T1 and T2 and the constancy of the others (T3 and T4) demonstrated the capacity of the experts to develop an accuracy aspect of their coordination. This evolution has for consequence an increase of the index of butterfly propulsion and a decrease of propulsive time out situated between the arm and leg propulsive actions. The evolution of arm and leg coordination with the increase of velocity directly influenced the IBP. This study showed the capacity of the expert swimmer in butterfly to develop an accuracy aspect of their coordination to optimise their propulsion.